2007
DOI: 10.1038/sj.mp.4002103
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a neuregulin 1 variant on white matter density and integrity

Abstract: Theories of abnormal anatomical and functional connectivity in schizophrenia and bipolar disorder are supported by evidence from functional magnetic resonance imaging (MRI), structural MRI and diffusion tensor imaging (DTI). The presence of similar abnormalities in unaffected relatives suggests such disconnectivity is genetically mediated, albeit through unspecified loci. Neuregulin 1 (NRG1) is a psychosis susceptibility gene with effects on neuronal migration, axon guidance and myelination that could potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
148
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 30 publications
7
148
1
Order By: Relevance
“…As the SNPs are in strong linkage disequilibrium, it is possible that both are indexing the same genetic effect. Although previous voxel-wise FA analyses have localized the effects of these SNPs to seemingly different anatomical regions, 6,7 the present data demonstrate that these effects may be common to a specific tract, the ATR.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…As the SNPs are in strong linkage disequilibrium, it is possible that both are indexing the same genetic effect. Although previous voxel-wise FA analyses have localized the effects of these SNPs to seemingly different anatomical regions, 6,7 the present data demonstrate that these effects may be common to a specific tract, the ATR.…”
contrasting
confidence: 67%
“…3 Neuregulin-1 (NRG1) is a gene associated with risk for schizophrenia 4 and bipolar disorder 5 as well as with white matter density and integrity in the medial prefrontal cortex 6 and the ALIC. 7 In this study, tractography reveals that these NRG1 effects can also be localized to the ATR.…”
mentioning
confidence: 66%
“…At the same time, our finding that the schizophrenia risk genotype predicts RT in the expected direction largely concurs with another study, which has reported ErbB4 genotype effects on neurocognitive measures in healthy controls (Nicodemus et al, 2006). The impact of schizophrenia risk NRG1 ErbB4 effects on left frontotemporal connectivity A Konrad et al genotypes on human WM has been shown in two DTI studies (McIntosh et al, 2007;Winterer et al, 2008). Therefore, our findings provide additional support for the notion that variations of the NRG1/ErbB4 signaling pathway might indeed be relevant for neuronal myelination.…”
Section: Discussionsupporting
confidence: 79%
“…Two recent diffusion tensor imaging (DTI) studies have reported schizophrenia risk NRG1 genotype effects on WM microstructure in human brain (McIntosh et al, 2007;Winterer et al, 2008). These studies thus support the notion that variations of the NRG1 gene might indeed be relevant for neuronal myelination as fractional anisotropy (FA) is thought to be an index of the degree of neuronal myelination (Davis et al, 2003).…”
Section: Introductionsupporting
confidence: 62%
“…[5][6][7] Identified risk variants of NRG-1 are associated with the reduced white matter volume that is observed in schizophrenic brains. 8 The NRG-1 gene spans 1.2 Mb 9 and gives rise to many structurally and functionally distinct isoforms, through alternative promoter usage. These isoforms are divided into three classic groups: 10 type I (previously known as acetylcholine receptor inducing activity, heregulin or neu differentiation factor), type II (glia growth factor) and type III (cysteine-rich domain containing), which are based on distinct amino termini.…”
Section: Introductionmentioning
confidence: 99%